+0  
 
0
941
1
avatar

f(x) = 3(x – 4)

Show that ff(x) = 9x – 48

thank you

Guest Jun 19, 2017
edited by Guest  Jun 19, 2017
 #1
avatar+94118 
+3

f(x) = 3(x – 4)

 

f [f(x)]=3 [3(x – 4) -4]

 

=3(3x-12-4)

=3(3x-16)

=9x-48

Melody  Jun 19, 2017

17 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.